PEMANFAATAN LAHAN KERING TADAH HUJAN PADA BUDI DAYA JAGUNG MANIS MELALUI TEKNOLOGI MPHP DI DESA BUKET DRIEN KABUPATEN ACEH TIMUR - Adnan; Muhammad Jamil; Safrizal (LPPM dan PM Universitas Samudra, 2020)
Bukit Drien Village is a non-beach village located 50 m below sea level, has 5 (five) hamlets, namely Bahagia Hamlet, Blang Meria Hamlet, Suka Damai Hamlet, Model Hamlet and Tualang Hamlet, with the number of Family Cards 334, Household Number 297 , the total population of 1,375 inhabitants consists of 704 men, 671 women. The farming system in Bukit Drien village is mostly rain fed. After the harvest is over, many paddy fields are left without any other agricultural activities, this is because people are still not accustomed to farming in the fields they just harvested. This will result in non-optimization of existing land use in order to increase community income in the Bukit Drien village. Even though the area of ​​paddy fields that can be utilized after harvest is quite extensive, and the community also has the ability to grow crops that have been passed down from generation to generation, as well as commodities to be cultivated also have considerable market potential as well, such as sweet corn.